A violência virtuosa em Dostoiévski e nos nossos dias - Paiva, Carla Jesuina Bento de (2010)
The present research has as objective to raise questions concerning the violence concept. The concept it is worked in the intersection of sociology, the psychoanalysis and literature. It is not any kind of violence, but that we call virtuous violence , that in the name of a greater good happens and is justified when violence is disguised as a virtue. For this, the conducting line of the research will be the psychic and social representations of the violence, supported in one of the basic concepts of the psychoanalysis, the impulse and the social justification that each season builds to justify their violence. For and, the violence virtue concept will find a frame, the book of Dostoiévski, Crime and Punishment, with the conflict of the main character Raskólnikov and his theory about the crime allowed